Adopción homoparental y el derecho a tener una familia en Ecuador - Gutiérrez Santamaría, Estefanía Belén (2022)
The focus of discussion of this scientific article is to determine whether the legal norm contained in article 68 (2) of the Constitution of the Republic of Ecuador "the adoption shall correspond only to couples of different sex", is constitutional and legitimate. Since, with the publication of judgments No. 10-18-CN/19 (same-sex marriage) and No. 11-18-CN/19 of the CCE (equal marriage) of the Constitutional Court of Ecuador, which recognizes the right of same-sex couples to marry and also details as a legitimate and constitutionally valid purpose pursued by Ecuador: constitute a family (by legal and de facto link) without discrimination and enjoy the protection of the State, another discussion was generated around genderless adoption, considering that the LGBTI + group, a minority group and historically discriminated against, is excluded from access to the aforementioned legal institution, thus limiting the exercise of certain of their fundamental and human rights. The scientific article will be displayed under the perspective of a normative-legal, socio-legal, ideological-legal and axiological-legal research. In addition, a dogmatic investigation will be developed applying an exegetical, teleological, systematic study, proportionality test and documentary technique; and sociological or empirical research, using the technique of interviewing child psychologists and a psychiatrist. Adoption in the Ecuadorian legal system will be analyzed, the rights of same-sex couples and children and adolescents will be cataloged, it will be verified whether the norm contained in article 68 (2) of the Constitution of the Republic of Ecuador is - or not - constitutional and legitimate, and legal situations will be identified for the application of genderless adoption. To conclude, by way of conclusion, it is determined that the norm is restrictive of rights, is not reasonable, is not proportional and does not guarantee or protect the best interests of the child.